Growth performance of Vallisneria spiralis under oligotrophic conditions supports its potential invasiveness in mid‐elevation freshwaters. (9th December 2014) - Bolpagni, R; Laini, A; Soana, E; Tomaselli, M; Nascimbene, J; Bohren, Christian
Summary Under the influence of human‐driven impacts, inland aquatic habitats of intermediate to mid‐high elevations may provide new areas for the establishment of lowland macrophytes that usually act as opportunistic species. Vallisneria spiralis, an obligate lowland macrophyte with an altitudinal range not exceeding 300 m, is a typical component of the plant diversity in meso‐ to eutrophic water habitats. This species is an engineering species in ecosystems, being able to modify the colonised sediments promoting its self‐maintenance under eutrophic conditions. Vallisneria spiralis delivers large amounts of oxygen to roots promoting the loss of nitrogen via denitrification and reducing the internal nutrient load of colonised environments. However, the establishment of the species results in rapid sediment accumulation and the progressive loss of more sensitive macrophytes. Furthermore, V. spiralis is one of the most widespread alien aquatic weeds in Europe. In this study, we evaluated the growth performance of V. spiralis under oligotrophic conditions at the upper limit of its altitudinal distribution using two different techniques: harvesting and leaf‐marking. Vallisneria spiralis proved to be able to grow under oligotrophic conditions, even if at rates lower than those recorded under eutrophic conditions. Accordingly, V. spiralis represents a potential threat for oligotrophic aquatic habitats at moderate elevations. However, the high variability observed in the growth responses highlights the need of further investigation to evaluate the key factors involved in the establishment and survival of the species.